Antimicrobial potential and mechanism of infant feces-derived Enterococcus faecalis in inhibiting Enterotoxigenic Escherichia coli - Xi Lu; Wei Sang; Lei Pan (Journal of Functional Foods)
Enterotoxigenic Escherichia coli (ETEC) is a leading cause of diarrhea in infants and travelers. However, antibiotic treatment is challenged by growing resistance. This study investigated the potential of Enterococcus faecalis, an early colonizer of the infant gut, as a probiotic to combat ETEC. From 125 healthy infant feces, 54 E. faecalis strains were isolated and evaluated for safety and function. E. faecalis LX25 and LX39 showed significant inhibition of ETEC growth, virulence gene (eltA and stA) expression (P < 0.05) and disrupted biofilm formation. Notably, LX39's cell-free supernatant (CFS) increased reactive oxygen species in ETEC, leading to cellular damage. HPLC revealed the three most concentrated organic acids, lactic (10.31 mg/mL), acetic (1.72 mg/mL) and citric acids (1.58 mg/mL) in LX39's CFS, which exceeding or approaching the MIC for ETEC. These findings indicate that E. faecalis LX39 could serve as effective probiotics candidates to inhibit ETEC, highlighting their potential in managing intestinal pathogen infection.